2010
DOI: 10.1097/cji.0b013e3181e4752e
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Denileukin Diftitox (DD) in Combination With High-dose Interleukin-2 (IL-2) for Patients With Metastatic Renal Cell Carcinoma (RCC)

Abstract: High-dose (HD) IL-2 is approved to treat renal cell carcinoma (RCC) with modest response rates and significant toxicity. Enhancement of cytotoxic T-cell activity by IL-2 is 1 mechanism of action. IL-2 also stimulates regulatory T lymphocytes (Tregs), which are associated with poor prognosis. Favorable outcomes are associated with greater rebound absolute lymphocyte count (Fumagalli 2003). DD depletes IL-2 receptor (CD25 component) expressing cells. We hypothesized that sequential therapy could complement each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…To date, all of these approaches are focusing on targeting CD25. The IL-2/diphtheria toxin fusion protein, denileukin diftitox (Ontak®, Eisai Inc., Woodcliff Lake, NJ, USA), has been reported to diminish Treg numbers in the circulation in some studies [90-92], although this has not been observed in all trials [93]. Various doses and schedules are being pursued, and clinical regressions have been reported in melanoma [94].…”
Section: Reviewmentioning
confidence: 99%
“…To date, all of these approaches are focusing on targeting CD25. The IL-2/diphtheria toxin fusion protein, denileukin diftitox (Ontak®, Eisai Inc., Woodcliff Lake, NJ, USA), has been reported to diminish Treg numbers in the circulation in some studies [90-92], although this has not been observed in all trials [93]. Various doses and schedules are being pursued, and clinical regressions have been reported in melanoma [94].…”
Section: Reviewmentioning
confidence: 99%
“…The only unusual AE was the development in a single patient of transient acantholytic dermatosis (Grover disease) concurrent with CLS, which was related to the IL-2 treatment [14]. Cardiac events (atrial fibrillation, infarction) occurred only in the study group (11 and 6 % respectively), as well as for malignant pleural effusion (6 %).…”
Section: Off-label Experiencementioning
confidence: 96%
“…Among 207 reports in the FAERS database, the most frequent events were CLS (28), pain (22), pyrexia (18), nausea/vomiting (17/18), hypotension (16), and dyspnea (14), and 3 cases of CRS.…”
Section: Postmarketing Surveillancementioning
confidence: 99%
“…Ontak has been used to treat CD25 + cutaneous T cell lymphoma ( 186 ). Ontak has also been tested with relatively positive results in peripheral T-cell lymphoma, metastatic renal cell carcinoma, and unresectable stage IV melanoma ( 187 189 ). Other studies of Ontak administration to melanoma patients, together with a DC vaccine reported no peripheral Treg depletion; yet, this result may be due to the use of a very low dose ( 190 ).…”
Section: Targeting Tregs As a Cure Research Strategymentioning
confidence: 99%